KNOWLEDGE OF HEALTHCARE PROVIDERS IN EXPANDED PROGRAM ON IMMUNIZATION, SA’ADAH, YEMEN - Qeran, Mohammed Ali; Habour, Ali Ba baker Ali; Hassan, Ehsan Hassab Elrasoul (Universal Journal of Pharmaceutical Research, 2023)
Background: After achieving high vaccination coverage, vaccine failure may occur. The sufficient knowledge of the workers in the expanded program of immunization (EPI) is one of the factors that affect in preventing this failure. In Saada, Yemen, there is no information about the knowledge of workers in the EPI. This study seeks to assess the knowledge of those in charge of immunization in Sa’adah, Yemen. Method: This prospective cross-sectional study was performed to assess healthcare providers (HCPs) knowledge regarding EPI. It was conducted on 60 HCPs in 60 H.F of 11 districts in Sa’adah Governorate, Yemen during 1 June – 30 July 2019. Appropriate interviewing pre-tested questionnaire was used to collect data from HCPs working in EPI. It includes the following: socio-demographic characteristics, knowledge about; cold chain and the method and time of administration of the vaccine and shake test. Face to face interview used to collect information. Data entering and cleaning were done using Microsoft Excel 2019 and exported to SPSS version 26, p-value less than 0.05 were considered significant. Differences in samples means were evaluated by chi-square test. Results: Age is one of the determining factors for knowledge of cold chain management (FET=0.040*), and the total knowledge score for of HCPs was (26.7%, 65%, and 8.3%) for good, fair, and poor knowledge, respectively. Conclusion: Only twenty-six-point seven of HCPs had a good knowledge score. Constant technical support and on job training to improve the HCPs knowledge about immunization are extremely recommended. Peer Review History: Received: 2 December 2022; Revised: 8 January; Accepted: 24 February 2023; Available online: 15 March 2023 Academic Editor: Dr. Emmanuel O. Olorunsola , Department of Pharmaceutics & Pharmaceutical Technology, University of Uyo, Nigeria, olorunsolaeo@yahoo.com Reviewers: Dr. Muhammad Zahid Iqbal, AIMST University, Malaysia, drmmziqbal@gmail.com Dr. Olanrewaju Rita-Marie Awotona, Legacy University, Banjul , The Gambia, olanrewajuadegbola@gmail.com Rola Jadallah, Arab American University, Palestine, rola@aauj.edu